Дослідження розподілу значень мікротвердості хромонікілевої сталі за допомогою статистичних методів - Дьяконенко, Ніна Леонідівна; Хацько, Наталія Євгенівна; Хацько, Кирило Олександрович (Харківський національний автомобільно-дорожній університет, 2022)
У роботі досліджуються розподіли мікротвердості фазових складових у сталі 14Х17Н2 за допомогою статистичних методів. Отримані результати підтверджується експериментальними вимірюваннями, що дає можливість їх практичного використання для визначення зносостійкості вузлів тертя.

Mathematical statistical methods are used to solve material science problems. New phases may be formed that are inherent only in this type of external action in the process of mechanical tests. In the presence of a multiphase structure, the use of the microhardness method provides measurement results that do not always correspond to the phase composition. In this regard, modeling the distribution of mi crohardness of phase components is of interest, since it allows obtaining indirect data on the processes that occur. The simulation of the experimental data on the microhardness values of chromium-nickel steel in the initial, hardened state and after mechanical friction tests were carried out using mathematical methods of the Microsoft Excel software package. Calculations have shown that both in the initial and quenched states, the set of micro hardness values of the ferrite – martensite matrix is described by a normal distribution curve (A = 0). However, the distribution curve for the hardened sample has a large dispersion (in the initial state 29 in the hardened – 47). This experiment can be explained by the fact that only a part of the grains undergoes martensitic transformation because of hardening, and their micro-hardness increases. Another part of the grains retains the ferrite structure. The average value increases from 336 kg / mm2 in the initial state to 510 kg/mm2 in the hardened state. Distribution curves of microhardness values of specimens that have passed mechanical friction tests have a completely different form. For them, the distribution curves of micro-hardness values have some asymmetry. In this case, for ferrite-martensite matrices, the asymmetry is positive (A = 0.59), and for the white zone it is negative (A = -0.59). This indicates that the formation of the white zone is preceded by an increase in the stress state of the matrix to a certain level. The obtained results of modeling the distribution of microhardness can be used to determine the wear resistance of the friction unit, which largely depends on the metal structure formed during the running-in process.
Studying the values of distribution of chromium nickel steel microhardness using statistical methods
Keywords: мікротвердість; сталь 14Х17Н2; структура; математичне моделювання; microhardness; steel 14Х17Н2; structure; statistical methods